Was federal parity associated with changes in Out-of-network mental health care use and spending? - Susan H. Busch; Emma E. Mcginty; Elizabeth A. Stuart; Haiden A. Huskamp; Teresa B. Gibson; Howard H. Goldman; Colleen L. Barry (BMC, 2017)
Abstract Background The goal of the Paul Wellstone and Pete Domenici Mental Health Parity and Addiction Equity Act is to eliminate differences in insurance coverage between behavioral health and general medical care. The law requires out-of-network mental health benefits be equivalent to out-of-network medical/surgical benefits. Insurers were concerned this provision would lead to unsustainable increases in out-of-network related expenditures. We examined whether federal parity implementation was associated with significant increases in out-of-network mental health care use and spending. Methods We conducted an interrupted time series analysis using health insurance claims from self-insured employers (2007-2012). We examined changes in the probability of using out-of-network mental health services and, conditional on out-of-network mental health service use, changes in the number of outpatient out-of-network mental health visits and total out-of-network mental health spending associated with the implementation of federal parity in 2010. Results From 2007 to 2012, the proportion of individuals receiving any out-of-network mental health services each month declined dramatically from 18 to 12%, with a one-time drop of 3 percentage points at parity implementation (p < .01). Among out-of-network mental health service users, there was an increase in the number of visits per month (.12 visits; p < .01) and total spending per month ($49; p < .01) at parity implementation. Although there was a one-time increase in spending at parity implementation, this increase was accompanied by an attenuation of a trend toward increased spending growth, such that spending was back to original predictions by the end of our study period. Conclusions Despite concerns expressed by the health insurance industry when federal parity was enacted, out-of-network mental health spending did not substantially increase after parity implementation. In addition, use of out-of-network mental health services appears to have contracted rather than expanded, suggesting insurers may have implemented other policies to curb out-of-network use, such as increasing access to in-network providers.